Understanding and modeling alternating tangential flow filtration for perfusion cell culture. (6th August 2014) - Kelly, William; Scully, Jennifer; Zhang, Di; Feng, Gang; Lavengood, Mathew; Condon, Jason; Knighton, John; Bhatia, Ravinder
<x xml:space="preserve">Abstract</x> Alternating tangential flow (ATF) filtration has been used with success in the Biopharmaceutical industry as a lower shear technology for cell retention with perfusion cultures. The ATF system is different than tangential flow filtration; however, in that reverse flow is used once per cycle as a means to minimize fouling. Few studies have been reported in the literature that evaluates ATF and how key system variables affect the rate at which ATF filters foul. In this study, an experimental setup was devised that allowed for determination of the time it took for fouling to occur for given mammalian (PER.C6) cell culture cell densities and viabilities as permeate flow rate and antifoam concentration was varied. The experimental results indicate, in accordance with D'Arcy's law, that the average resistance to permeate flow (across a cycle of operation) increases as biological material deposits on the membrane. Scanning electron microscope images of the post‐run filtration surface indicated that both cells and antifoam micelles deposit on the membrane. A unique mathematical model, based on the assumption that fouling was due to pore blockage from the cells and micelles in combination, was devised that allowed for estimation of sticking factors for the cells and the micelles on the membrane. This model was then used to accurately predict the increase in transmembane pressure during constant flux operation for an ATF cartridge used for perfusion cell culture. © 2014 American Institute of Chemical Engineers Biotechnol. Prog., 30:1291–1300, 2014